2015
DOI: 10.1186/s12871-016-0225-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factor-1 alpha and prolinhydroxlase 2 polymorphisms in patients with severe sepsis: a prospective observational trial

Abstract: BackgroundHypoxia-inducible-factor-1α (HIF-1α) and HIF-1 degrading prolyl-hydroxylases (PHD) are key regulators of the hypoxic-inflammatory response. Functionally active genetic variants in the HIF-1α (C/T; Single Nucleotide Polymorphism (SNP) rs11549465) and the PHD2 gene (EGLN1; C/T; SNP rs516651 and T/C; SNP rs480902) are associated with altered HIF-1α mRNA nuclear translocation and an altered adaptation to hypoxia. Furthermore, the HIF system is important in surviving inflammatory disorders and sepsis. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Cytokine concentrations were assessed from EDTA-plasma and cell culture supernatant using the Procarta multiplex cytokine kit (Affymetrix, Santa Clara, CA, USA) following the manufacturer's protocol as published previously [6,23]. In detail, plasma and supernatant concentrations of proinflammatory cytokines (Interleukin-3 (IL-3), Interleukin-6 (IL-6), tumor necrosis factor α (TNFα), anti-inflammatory cytokines (Interleukin-1 receptor antagonist (IL-1RA), Interleukin-10 (IL-10)), chemokines (chemokine C-C motif ligand 2/monocyte chemotactic protein 1 (CCL-2/MCP-1), C-X-C motif chemokine 12/stromal cell-derived factor 1 (CXCL-12/SDF-1α), and vascular endothelial growth factor A (VEGF-A) were measured at all four timepoints [55].…”
Section: Cytokine Measurements From Plasma and Supernatantmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokine concentrations were assessed from EDTA-plasma and cell culture supernatant using the Procarta multiplex cytokine kit (Affymetrix, Santa Clara, CA, USA) following the manufacturer's protocol as published previously [6,23]. In detail, plasma and supernatant concentrations of proinflammatory cytokines (Interleukin-3 (IL-3), Interleukin-6 (IL-6), tumor necrosis factor α (TNFα), anti-inflammatory cytokines (Interleukin-1 receptor antagonist (IL-1RA), Interleukin-10 (IL-10)), chemokines (chemokine C-C motif ligand 2/monocyte chemotactic protein 1 (CCL-2/MCP-1), C-X-C motif chemokine 12/stromal cell-derived factor 1 (CXCL-12/SDF-1α), and vascular endothelial growth factor A (VEGF-A) were measured at all four timepoints [55].…”
Section: Cytokine Measurements From Plasma and Supernatantmentioning
confidence: 99%
“…In this context, we have previously shown that additionally to the extent of hypoxic or inflammatory stimuli or their duration, genetic variants in HIF-1, HIF-2, and HIF-degrading PHD-2 alter human adaptation to hypoxia [15][16][17][18][19]. High altitude residents thus have blunted hypoxic ventilatory response and diminished pulmonary hypertension under hypoxia [20,21], increased heart rate, improved peripheral oxygen saturation, and reduced incidence of mountain sickness, as assessed using the Lake Louise Score (LLS) [15,16,[22][23][24]. LLS, which has recently been revised, is a well-established tool to evaluate the severity of acute mountain sickness (AMS) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Functionally active genetic variants in HIF-1 and PHD2 can impact on HIF-1α mRNA expression. However, they are not independent risk factors for 30-days mortality in severe sepsis (Höcker et al, 2015). A clinical trial investigating the potential of HIF-1 as a novel biomarker in septic shock has now been completed and data on the primary outcomes remains to be published (NCT02163473).…”
Section: Hifmentioning
confidence: 99%
“…Similarly, Textoris et al have reported the independence of the expression of HIF-1 and outcomes of patients with sepsis [ 19 ]. Höcker and his coworkers have further announced that the expression of HIF-1α cannot alter 30-day mortality in severe sepsis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%